2020
DOI: 10.1002/chem.202003611
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Boron into Uranium Metallacycles: Synthesis, Structure, and Reactivity of Boron‐Containing Uranacycles Derived from Bis(alkynyl)boranes

Abstract: The reaction of uranacyclopropene complex (C5Me5)2U[η2‐1,2‐C2(SiMe3)2] with B‐aryl bis(alkynyl)borane PhB(C≡CPh)2 led to the first six‐membered uranium metallaboracycle, while the reaction with B‐amino bis(alkynyl)borane (Me3Si)2NB(C≡CPh)2 afforded an unexpected uranaborabicyclo[2.2.0] complex via [2+2] cycloaddition. The reaction with CuCl revealed the non‐innocent property of the rearranged bis(alkynyl)boron species towards oxidant. The reactions with isocyanide DippNC: (Dipp=2,6‐iPr2‐C6H3) and isocyanate tB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 72 publications
0
11
0
5
Order By: Relevance
“…In a series of publications, it was shown that it is possible to transfer the typical alkyne substitution reactivity of group 4 metallocene bis­(trimethylsilyl)­acetylene complexes to actinide metallacycles as well. , For this several papers from Zi, Walter, et al as well as from Kiplinger and co-workers , about synthesis and reactions of actinide metallocene bis­(trimethylsilyl)­acetylene complexes Cp′ 2 M­(η 2 -Me 3 SiC 2 SiMe 3 ) were published.…”
Section: Actinide Metallocene Bis(trimethylsilyl)acetylene Complexesmentioning
confidence: 84%
See 2 more Smart Citations
“…In a series of publications, it was shown that it is possible to transfer the typical alkyne substitution reactivity of group 4 metallocene bis­(trimethylsilyl)­acetylene complexes to actinide metallacycles as well. , For this several papers from Zi, Walter, et al as well as from Kiplinger and co-workers , about synthesis and reactions of actinide metallocene bis­(trimethylsilyl)­acetylene complexes Cp′ 2 M­(η 2 -Me 3 SiC 2 SiMe 3 ) were published.…”
Section: Actinide Metallocene Bis(trimethylsilyl)acetylene Complexesmentioning
confidence: 84%
“…This was reported for different symmetrically and nonsymmetrically substituted alkynes to yield a wide variety of well-known metallacycles (metallacyclopentadienes, metallacyclocumulenes/metallacyclopentatrienes, metallacyclopentenes). Reactions with 9,10-phenanthrenechinone gave a monomeric uranium quinonate, whereas o -benzochinone furnished a dimeric quinonate . Very recently the synthesis, structure, and reactivity of well-defined scandacyclopropenes were described as well .…”
Section: Actinide Metallocene Bis(trimethylsilyl)acetylene Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gratifyingly, the reaction of I with Ph 2 BCl yielded 3 , which was in full agreement with our hypothesis. In solution, complex 3 showed a broad resonance at δ B 83.9, which is comparable to that of Ph 2 BMe ( δ B 70.6) [15] and an isolable uranium metallaboracycle ( δ B 76.0) [16] . The single crystal structure of 3 revealed a dangling trigonal planar Ph 2 B(alkyl) moiety as indicated by the sum of angles (360.0°) around the boron center.…”
Section: Figurementioning
confidence: 94%
“…In solution, complex 3 showed a broad resonance at δ B 83.9, which is comparable to that of Ph 2 BMe (δ B 70.6) [15] and an isolable uranium metallaboracycle (δ B 76.0). [16] The single crystal structure of 3 revealed a dangling trigonal planar Ph 2 B(alkyl) moiety as indicated by the sum of angles (360.0°) around the boron center. The trigonal bipyramidal geometry around the uranium nucleus in 3 resembles its precursor I.…”
mentioning
confidence: 98%